The Influence of SHRM and Organizational Culture on Digital HR Transformation in Public Sector Agencies - Dian Intan Tangkealo; Srisetyawanie Bandaso; Marniati (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The digital era demands innovative human resource management strategies and supportive organizational cultures to enhance public sector efficiency, yet their integration remains underexplored in local government contexts. this study aims to examine how strategic human resource management and organizational culture drive digital human resource management transformation in North Toraja Regency, focusing on developing an integrative model to improve bureaucratic responsiveness. A quantitative approach with a causal-associative design was employed, involving 359 civil servants selected through purposive sampling. Data were collected via questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares. The findings confirm that strategic human resource management positively influences digital human resource management transformation by enhancing workforce digital capabilities. Organizational culture also significantly contributes by fostering adaptability and openness to technological change. Additionally, strategic human resource management shapes a collaborative and innovative culture, strengthening transformation efforts. These results highlight the synergy of strategic human resource management and organizational culture in advancing digital transformation in North Toraja’s local government. The study concludes that aligning human resource strategies with cultural reforms is essential for effective digital transformation, offering practical insights for local governments to enhance digital competencies and bureaucratic efficiency.